2016
DOI: 10.1002/bem.21970
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic and genotoxic potential of direct electric current in Escherichia coli and Salmonella thyphimurium strains

Abstract: Direct electric current has several therapeutic uses such as antibacterial and antiprotozoal action, tissues scarring and regeneration, as well as tumor treatment. This method has shown promising results in vivo and in vitro, with significant efficacy and almost no side effects. Considering lack of studies regarding direct electric current mutagenic and/or genotoxic effects, the present work evaluated both aspects by using five different bacterial experimental assays: survival of repair-deficient mutants, Salm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Additionally, the metastasis can be favored because the cathode (electrode with negative polarity) repels negatively charged tumor cells [Haltiwanger, ]. These two aspects should not be underestimated during EChT application, although some authors report that DC does not induce metastasis [Zhou et al, ] or mutagenic and genotoxic effects [Gomes et al, ]. On the other hand, the treatment of metastatic lesions may be effective when DC is combined with nanoparticles [Campos et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the metastasis can be favored because the cathode (electrode with negative polarity) repels negatively charged tumor cells [Haltiwanger, ]. These two aspects should not be underestimated during EChT application, although some authors report that DC does not induce metastasis [Zhou et al, ] or mutagenic and genotoxic effects [Gomes et al, ]. On the other hand, the treatment of metastatic lesions may be effective when DC is combined with nanoparticles [Campos et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies developed with direct electric current indicated the importance of pH variation in tumoral [Veiga et al, ; Cury et al, ; Holandino et al, ] and non‐tumoral damage [Gomes et al, , ]. For that reason, pH variation was registered with the same values of electric charge previously evaluated in cell viability experiments.…”
Section: Resultsmentioning
confidence: 89%
“…In the present work, DC effects on C. albicans were evaluated using platinum electrodes since it is an inert material and consequently does not induce ion release in the electrolytic medium, facilitating DC mechanism comprehension, as previously registered in bacteria [Holandino et al, ; Gomes et al, ] and protozoa [Gomes et al, ] samples. The viability assays were performed by two methods: plating to quantify CFUs and propidium iodide (PI) incorporation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations